PENERAPAN METODE PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN DIAGRAM VEE TERHADAP KETERAMPILAN PROSES SAINS PADA MATERI TERMOKIMIA BERBASIS VIRTUAL LAB - Aulia Sanova (Universitas Batanghari Jambi, 2014)
This is an experimental study, where the experimental class was taught by Problem Based Learning (PBL) method – assisted by Vee diagrams using virtual media lab and control class was taught by direct instruction methods without the use of virtual media. This study aims to find out the responses of students toward the methods and media used and the effect of the use of the PBL method assisted by Vee diagram in thermo chemical material using virtual media lab to the students’ skill on science process.The populations in this study were students of Chemical Education who took Thermo chemical subject in the second semester of academic year 2012/2013. Sampling technique in this study was non-random sampling technique based on purpose. Data collection techniques for measuring the science process skill used analytical test methods and observations (observation), while the response of students toward the methods and media used can be determined from the questionnaire.This study found out that there are differences in improvement of science process skills of students who were taught by PBL method with students who are taught by the direct method. The results data analysis is also parallel to the student responses related to methods and media used. Where 92 % of students were interested in learning patterns and 94 % of students responded if the learning pattern is very beneficial for them so, indirectly it can measure the extent to which attitudes of students in the learning process skills .Keyword : Problem Based Learning, Diagram Vee,Virtual Lab, Termokimia.